2013
DOI: 10.1021/ol401041f
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of α-Bromo Enones with 1,2-Diamines. Cascade Assembly of 3-(Trifluoromethyl)piperazin-2-ones via Rearrangement

Abstract: A facile one-pot synthesis of 3-trifluoromethylated piperazin-2-ones has been achieved by the treatment of trifluoromethyl 2-bromo enones with N,N'-disubstituted ethylenediamines in trifluoroethanol. The mechanism of this unexpected reaction is discussed in terms of multistep processes involving formation of captodative aminoenone as a key intermediate. The unique influence of trifluoromethyl group on the reaction path was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 27 publications
3
18
0
Order By: Relevance
“…However, the expected trifluoroacetylpiperazines 12 were obtained only with the dicyclopropyl derivative of ethylenediamine. To our great surprise, in all other cases in which bromoenones reacted with N , N′ ‐dialkylethylenediamines the isomeric piperazinones 11 were isolated in good to excellent yields , . It should be emphasized that the piperazinones obtained are a very rare type of heterocycles and that, to the best of our knowledge, no other methods for their assembly are yet known.…”
Section: Reactions With Nucleophilessupporting
confidence: 66%
“…However, the expected trifluoroacetylpiperazines 12 were obtained only with the dicyclopropyl derivative of ethylenediamine. To our great surprise, in all other cases in which bromoenones reacted with N , N′ ‐dialkylethylenediamines the isomeric piperazinones 11 were isolated in good to excellent yields , . It should be emphasized that the piperazinones obtained are a very rare type of heterocycles and that, to the best of our knowledge, no other methods for their assembly are yet known.…”
Section: Reactions With Nucleophilessupporting
confidence: 66%
“…It was demonstrated that the reaction of bromoenone 1 a with N , N ′‐dimethylethylenediamine (DMEDA) resulted in formation of unexpected 3‐trifluoromethyl‐piperazine‐2‐ones, the formation of which is a result of skeletal rearrangement with migration of the trifluoromethyl group in adjacent position 5. Predictable 2‐acyl piperazines9 were not formed.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction was found to be very general to afford trifluoromethylated piperazinones 3 in good to high yields. (Scheme ) The structures of compounds 3 were elucidated unambiguously using a combination of various NMR methods; the ultimate confirmation of the structures was achieved by X‐ray diffraction analysis of 3 g 5…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method utilizes a strong base as catalyst for a Michael addition and ring-closure reaction of vinyl selenone 374 [221] revealed an exclusive process for the synthesis of piperazin-2-ones in trifluoroethanol via the formation of captodative aminoenone intermediates 379 generated from the corresponding trifluorobromoenones 377 and N ,N -disubstituted ethylenediamines 378 at room temperature (Scheme 108, Path A). An efficient four-component Ugi-reaction has been studied for the preparation of piperazines 380 from diversely substituted aldehydes, cyanides, phenols, and aminoacetaldehyde dimethyl acetal (381, 382, 383, 384, respectively) under mild reaction condition as shown in Scheme 108 (Path B).…”
Section: Synthesis Of Piperazinesmentioning
confidence: 99%